Integral Sequence

Calculus Level 3

Define a sequence of functions { f n ( x ) } \{f_n(x)\} as follows: f 1 ( x ) = 1 , f n + 1 ( x ) = 0 e t x f n ( t ) d t . f_1(x) = 1, \hspace{.4cm} f_{n+1}(x) = \int_0^{\infty}\frac{e^{-tx}}{f_n(t)}dt. Evaluate: f 20 ( 1 ) f 21 ( 1 ) f 18 ( 1 ) f 19 ( 1 ) \frac{f_{20}(1)f_{21}(1)}{f_{18}(1)f_{19}(1)}


The answer is 342.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Discussions for this problem are now closed

Jatin Yadav
Apr 11, 2014

Checking f 1 f_{1} , f 2 f_{2} , etc. we get to know that f n ( x ) f_{n} (x) can be expressed as a n x n 1 \displaystyle \frac{a_{n}}{x^{n-1}}

f n + 1 x = 1 a n 0 x n 1 e x t d t f_{n+1} x = \displaystyle \frac{1}{a_{n}} \int_{0}^{\infty} x^{n-1} e^{-xt} dt

Using integration by parts using e x t e^{-xt} as first function, and x n 1 x^{n-1} as second function, we get:

f n + 1 ( x ) = x n a n 0 x n e x t d t \displaystyle f_{n+1} (x) = \displaystyle \frac{x}{n a_{n}} \int_{0}^{\infty} x^{n} e^{-xt} dt

f n + 1 ( x ) = x n a n a n + 1 f n + 2 ( x ) \displaystyle \Rightarrow f_{n+1} (x) = \displaystyle \frac{x}{n a_{n}} {a_{n+1}} f_{n+2} (x)

Put f n + 1 ( x ) = a n + 1 x n \displaystyle f_{n+1} (x) = \frac{a_{n+1}}{x^n} , and f n + 2 ( x ) = a n + 2 x n + 1 \displaystyle f_{n+2} (x) = \frac{a_{n+2}}{x^{n+1}} to get :

a n + 2 = n a n a_{n+2} = n a_{n}

Now, At x = 1 x=1 , our expression is a 20 a 21 a 18 a 19 = 18 × 19 = 342 \displaystyle \frac{a_{20} a_{21}}{a_{18} a_{19}} = 18 \times 19 = 342

Logan Dymond
Apr 10, 2014

We claim that

f n ( x ) = ( n 2 ) ! ! x n 1 f_n(x) = \frac{(n-2)!!}{x^{n-1}}

for n > 1 n>1 where n ! ! n!! is the double factorial. We proceed by induction.

We see that, f 2 ( x ) = 0 e t x d t = 1 x f_2(x) = \int_0^{\infty}e^{-tx}dt = \frac{1}{x}

Assume that for n = k > 1 n=k>1 ,

f k ( x ) = ( k 2 ) ! ! x k 1 f_k(x) = \frac{(k-2)!!}{x^{k-1}}

Then, for n = k + 1 n=k+1 , we have,

f k + 1 ( x ) = 0 e t x f k ( t ) d t = 0 t k 1 e t x ( k 2 ) ! ! d t f_{k+1}(x) = \int_0^{\infty}\frac{e^{-tx}}{f_k(t)}dt = \int_0^{\infty}\frac{t^{k-1}e^{-tx}}{(k-2)!!}dt

and by repeated integration by parts,

= 1 ( k 2 ) ! ! ( t k 1 e t x x ( k 1 ) t k 2 e t x x 2 ( k 1 ) ( k 2 ) t k 3 e t x x 3 + ( k 1 ) ! e t x x k ) 0 =\frac{1}{(k-2)!!}\left(\frac{-t^{k-1}e^{-tx}}{x} - \frac{(k-1)t^{k-2}e^{-tx}}{x^2} - \frac{(k-1)(k-2)t^{k-3}e^{-tx}}{x^3} + \dots - \frac{(k-1)!e^{-tx}}{x^k}\right)\big|_0^{\infty}

Note that as t t\to\infty , each term goes to 0 0 , and as t 0 t\to0 , each term except for the last also goes to 0 0 . Thus the integral is equal to

( k 1 ) ! ( k 2 ) ! ! x k = ( k 1 ) ! ! x k \frac{(k-1)!}{(k-2)!!x^k} = \frac{(k-1)!!}{x^k}

Thus,

f 20 ( 1 ) f 21 ( 1 ) f 18 ( 1 ) f 19 ( 1 ) = 18 ! ! 19 ! ! 16 ! ! 17 ! ! = 19 ! 17 ! = 18 19 = 342 \frac{f_{20}(1)f_{21}(1)}{f_{18}(1)f_{19}(1)} = \frac{18!!19!!}{16!!17!!} = \frac{19!}{17!} = 18*19 = \boxed{342}

Why two factorial signs?

Oliver Bel - 7 years, 1 month ago

It's the double factorial

Logan Dymond - 7 years, 1 month ago

Brilliant problem!

Ahaan Rungta - 7 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...